Perlindungan Konsumen Terhadap Jamu Tradisional Ilegal Berbahaya di Kota Serang Banten - Nadila Dwi Rahmawati; Aris Prio Agus Santoso; Hery Dwi Utomo (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
This study examines consumer protection efforts against the distribution of hazardous illegal traditional herbal medicines in Serang City, Banten. The widespread circulation of such products—particularly those containing Chemical Drugs (Bahan Kimia Obat/BKO) and lacking distribution permits—poses a significant threat to public health. Between 2020 and 2025, the Inspection Division of the Food and Drug Monitoring Agency (BBPOM) in Serang secured and destroyed approximately 706 items, totaling 6,841 units, with an estimated economic value of IDR 91,158,350. The research focuses on two main issues: the mechanisms for protecting consumers from dangerous illegal traditional herbal medicines in Serang City, and the role of BBPOM in supervising their circulation. Employing an empirical juridical method with a qualitative-descriptive approach, the study collected data through literature reviews, documentation, and interviews with BBPOM Serang officials. The findings indicate that consumer protection is carried out through both preventive and repressive measures. Preventive efforts involve pre-market and post-market supervision to ensure that products meet safety and regulatory standards before and after they enter the market. Repressive actions include law enforcement against violations, confiscation and destruction of illegal products, and the imposition of administrative and criminal sanctions on offenders. BBPOM Serang plays a pivotal role in monitoring illegal herbal medicines by conducting regular inspections, surveillance, and investigations of production and distribution facilities, as well as educating the public about the dangers of unsafe products. Nevertheless, supervision efforts are hindered by challenges such as low public awareness regarding product safety and economic pressures that drive some producers and sellers to ignore legal requirements. Strengthening collaboration between regulatory agencies, law enforcement, and community stakeholders is essential to improving consumer protection and ensuring the circulation of safe traditional herbal products in the region.